The concept of basic income: global experience and implementation possibilities in Lithuania - Laurinavičius, Algimantas; Laurinavičius, Antanas (Business, Management and Economics Engineering, 2016)
The article gives an overview of universal basic income as one of the instruments of the asset-based policy, analyses its theoretical concept and practical examples. Latest trends in Europe, especially in Finland and Switzerland, are overviewed and possibilities to implement such an instrument in Lithuania are evaluated. Research methods of scientific literature analysis, comparative and logical analysis of statistical data, data grouping and presentation were used. Article finds out that the concept of basic income is being implemented on a small scale in the US state of Alaska and in a small autonomous territory of China – Macao. Finland and Switzerland are determined to fully implement the concept of basic income by providing monthly benefits to all their citizens. Although Lithuania is categorized as a country with high income inequality and high level of poverty risk, currently it is not possible to implement the concept of basic income in Lithuania: the state social insurance fund budget would not be able to fund sufficient benefits, and the benefits that could be provided by the budget would not comply with the objectives of the concept of basic income.